Influence of Ageing Conditions on the Residual Stresses Development, Thermomechanical and Chemical Properties of Epoxy Amine Coatings - Ng, Janice Xin Yee (Curtin University, 2024)
The influence of different ageing conditions on the development of residual stresses, thermomechanical, and chemical properties of an epoxy amine coating was investigated in this thesis. A holistic approach, integrating computational simulations, experimental assessments, and theoretical calculations, was employed to analyse the effects of ageing conditions on the coating's properties. Furthermore, a structured approach for the determination of thermomechanical properties and a coherent framework for the determination of the coefficient of hygroscopic expansion (CHE) of the coating were presented. Additionally, insight on degradation mechanisms was provided through the utilisation of different characterisation techniques such as time-of-flight secondary ion mass spectroscopy (ToF-SIMS) coupled with principal component analysis (PCA), and Fourier transform infrared spectroscopy (FTIR). The feasibility of the residual stress calculation approach was validated, revealing a significant correlation between residual stresses, thermomechanical responses, and chemical properties variation of the coating. Overall, this research contributed significantly to the field of organic coatings, enhancing comprehension of the effects of various ageing conditions and offering insightful strategies for the optimisation of coating formulations and improvement of industrial practices to ensure reliability and structural integrity of coated and insulated parts across industries.